Zinc and vitamin C deficiency in a newborn with low gestational age. - Buquicchio, R.; Laforgia, N.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2004)
A premature with 24-week gestational age, fed by total parenteral nutrition and affected by ileo-umbilical stercoraceous fistula is reported. At the end of the second month the little baby presented the characteristic clinical features of acrodermatitis enteropathica. The latter responded rapidly to zinc supplementation. In the meantime the little baby presented a tumefaction of the left thigh, multiple ecchymoses, ulaemorrhagia and stomatitis. Thanks to vitamin C supplementation, the clinical features of avitaminosis C rapidly regressed. Unfortunately, the little baby died when aged 6 months due to the complications of necrotizing enterocolitis. To the best of our knowledge, this is the first case of simultaneous deficiency of vitamin C and zinc.